Development of the Book Home 1: A Childrens`s Fiction Based on Mental Health and Montessori Paradigm (Set Within a Muslim Family Background) - Anugrah Putri, Weni Tria; Nur Dahlia, Dwi Ulfa; Mukti, Beta Pujangga; Ahmadi, Ahmadi (IAIN Ponorogo, 2024)
This research aims to determine the intrinsic elements that will be used as a basis for developing Home 1: A children's fiction with mental health nuances and Montessori paradigm (set within a Muslim Family background); describe the development process; and the results of its development. This research is Research and Development with the Borg and Gall flow. However, the Borg and Gall path taken in this research only reached stage six, namely product development and validation testing. This product development is aimed at children aged 5 to 7 years. The use of this product is expected to continue with parental assistance. Some of the characters in this product include Lili, mama, and papa. In the validation test results, a good score was obtained, and it was considered capable of being developed. This research uses research data collection techniques in the form of observation. The result of this research is a draft of HOME 1 which consists of 10 fiction titles. As a continuation of the study, it is necessary to develop HOME 2 with a different fiction title. However, this text only mentions one storyline that represents the overall content in HOME 1.